Hoyt Sanford Vandenberg papers - Vandenberg, Hoyt Sanford, 1899-1954.
Correspondence, memoranda, diaries, speeches, articles, reports, appointment books, mail logs, personal files, accounts, and printed matter relating chiefly to Vandenberg's service as chief of staff of the U.S. Air Force. Documents the growth and development of the U.S. Air Force during that period as well as its participation in the Korean War. Correspondents include Lindley Beckworth, Omar Nelson Bradley, Overton Brooks, J. Lawton Collins, Clyde Roark Hoey, Olin D. Johnston, John F. Kennedy, Scott Wike Lucas, George E. Stratemeyer, Harry S. Truman, and Carl Vinson.
Air Force officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Beckworth, Lindley -- Correspondence; Bradley, Omar Nelson, -- 1893-1981 -- Correspondence; Brooks, Overton, -- 1897-1961 -- Correspondence; Collins, J. Lawton -- Correspondence; Hoey, Clyde Roark, -- 1877-1954 -- Correspondence; Johnston, Olin D. -- 1896-1965 -- Correspondence; Kennedy, John F. -- 1917-1963 -- Correspondence; Lucas, Scott Wike, -- 1892-1968 -- Correspondence; Stratemeyer, George E., -- 1890-1970 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Vinson, Carl, -- 1883-1981 -- Correspondence; United States. -- Air Force. -- Office of the Chief of Staff; Aeronautics, Military; Korean War, 1950-1953.; Korean War, 1950-1953 -- Aerial operations; Air Force officers